Propuesta de un plan estratégico de comunicación para el gobierno autónomo descentralizado municipal del Cantón Santa Rosa, con el fin de fortalecer su identidad acorde a su manual de marca - Iñiguez Parra, Gabriel Antonio (2014)
The following graduation work was carried out in the canton Santa Rosa in the province of El Oro, where and as background, the Municipal Government concerned about the need to boost his image, he hired a company advertising that final product to the consulting delivered a Manual containing only the technical and graphical specifications using the mark Santa Rosa, aside strategies dimension of the image and identity of Canton, thereby impacting on a tiny number of all potential strategic audiences. Given the fundamental missing and as a final graduation work master, proceeded with the implementation of a proposed strategic plan communication from DirCom perspective action began with a split on interviews with decision makers research, surveys santarroseños and development of focus groups, in order to triangulate the information and get an overview of the need to analyze and project the identity of the Sector environment. Strategic Public Communication Plan is characterized from the methodology of Professor Doctor Marcelo Manucci, who divides stakeholders according to the proposal of Image and Brand. Finally, the Strategic Communication Plan proposes obtained align communication activities in three programs that arise from analysis of the outcome of the research chapter, where the first stage of information given to familiarize the public of the organization, in the second given to public participation which assist the implementation of actions and in the last phase calls for integration as key to achieving the same method loyalty.